β-Adrenergic-induced CD40 overexpression on gingival fibroblasts: role of PGE2 - Furlán, César (2010)
CD40, a member of the tumour necrosis factor-α receptor family, is constitutively expressed by cells of haematopoietic and non-haematopoietic origin, including fibroblasts. Signalling through this receptor molecule regulates inflammatory mediator secretion by many cell types. The work has been performed in healthy subjects and the authors studied, by cellular culture, flow cytometric analysis and ELISA assay, the expression of CD40 and PGE2 (prostaglandin E2) generation on gingival fibroblasts stimulated by β-AR (β-adrenoceptor) agonists. Herein, the authors demonstrate that β-AR subtype activation via their own specific agonists markedly increased CD40 expression on human gingival fibroblasts. This effect was prevented by β-AR subtype-specific antagonists. In addition, gingival fibroblast β-AR stimulation resulted in an increase in PGE2 generation. The inhibition of PLA2 (phospholipase A2) and COX-1 (cyclo-oxygenase-1) but not COX-2 impaired β-AR increase of PGE2, an effect that was restored by the addition of low concentrations of PGE2, suggesting that PGE2 generation is implicated in the mechanism underlying β-AR-agonist-mediated CD40 overexpression. Our work has revealed an endogenous β-AR mediator network involving gingival fibroblasts.